A mixed methods study investigating the impact of the Homunculi Approach on anxiety for children with social communication needs - Brown, Kathryn (2024)
The mental health of children and young people is of growing concern nationally. Schools are well placed to support children with their mental wellbeing, and Educational Psychologists play an important role in assisting schools to adopt evidence-based practices to best support children. One approach with a wealth of research exploring its effectiveness is Cognitive Behavioural Therapy (CBT), but less is known about the efficacy of CBT based approaches when they are delivered in school settings.